PENGARUH ROA TERHADAP FDR PADA LAPORAN KEUANGAN BANK SYARIAH INDONESIA TAHUN 2019 – 2023 - Salma Pratiwi; Annisa Khoiro Az-zahra, Hanani, Farizi Abdullah, Haikal Wijaya, Bopi Saputra, Desi Armaria, Nurhafia (CV. ADIBA AISHA AMIRA, 2024)
This study aims to examine the effect of Rentability Ratio (ROA) on Liquidity Ratio (FDR) and evaluate the financial performance of PT. Bank Syariah Indonesia (BSI). The data used was obtained from BSI's financial statements. The research method used is quantitative research. This study uses multiple linear regression analysis as the analysis technique, and sampling uses the purposive sampling technique. Based on the study, it shows that Return on assets (ROA) has no effect on the Financing to Deposit Ratio (FDR). This shows that the impact of FDR on ROA is not affected by an increase or decrease